Episodic memory training in elderly: A systematic review - Mendonça, André Rocha; Loureiro, Lucas Machado; Nórte, Carlos Eduardo; Landeira-Fernandez, Jesus (Frontiers in Psychology, 2022)
Introduction: Episodic memory is a cognitive process that allows the recall of experiences, learning, and the pursuit of future goals. During the aging process, episodic memory declines negatively, impacting social and psychological aspects in the elderly. Such intervention strategies as cognitive training are non-pharmacological ways of reducing these losses. Objective: We systematically reviewed studies of the cognitive training of episodic memory in healthy elderly individuals and elderly individuals with clinical conditions. Method: We systematically searched the PubMed, PsycNET, Web of Science, and SciELO databases using the descriptors “Episodic Memory” AND “Training” AND “Elderly” OR “Aging” OR “Dementia” in English and translated into Portuguese. Results: Of the 572 articles that were identified by the search, 23 were included in the final analysis. The main variables that comprised the intervention protocols (i.e., characteristics of the sample, type of control group, mode of episodic memory training, and duration of training) were investigated, as well as the outcome variables, efficacy, and risk of bias. The main results indicated effectiveness with regard to different forms of the cognitive training of episodic memory. Conclusion: Episodic memory training among the elderly can mitigate the negative effects of cognitive decline in dementia and healthy subjects promoting impacts at social, psychological, and economic levels. Although it is a widely studied topic, further empirical studies on the utility of episodic memory training in healthy elderly individuals and elderly individuals with clinical conditions are still needed.